Armour and Weapons in Tibet from Yongle to Younghusband - La Rocca, Donald (Edizioni Ca’ Foscari, 2021)
This paper presents an overview of the origins and development of research into various types of arms and armour used in Tibet from approximately the fifteenth century to the early twentieth century. Incorporated into this are a brief survey of well recognised examples and a review of the wide multiplicity of rare and less familiar forms, including helmets, armour for men and horses, swords, and firearms, many of which have only come to light over the past twenty-five years.